Factors affecting use of personal protective equipment and pesticide safety practices: A systematic review - Ratana Sapbamrer (2020)
© 2020 Elsevier Inc. An evidence-based understanding of factors influencing PPE use and pesticide safety practices has the benefit of facilitating the design of interventions to minimize exposure to pesticides and the promotion of the utilization of PPE and safety practices among agricultural pesticide handlers. The aim of this study, therefore, is to review the available literature on the use of PPE in agricultural pesticide handlers in world regions, and also the factors associated with the use of PPE and pesticide safety practices in farmers and farm workers. Full-text articles published on PubMed, Scopus, and ISI databases between 1999 and 2019 were reviewed and the scientific evidence was evaluated. One hundred and twenty-one articles were eligible for inclusion in this quantitative synthesis: 110 evaluated PPE use in agricultural pesticide handlers, and 23 focused on factors affecting PPE use and pesticide safety practices. Considerable evidence was found to show that the most basic PPE worn among pesticide handlers in all world regions was a long sleeve shirt (66.1%), long sleeve trousers (71.1%), and a hat (47.3%). The lowest basic PPE worn was an apron (8.6%), goggles (24.3%), gloves (40.5%), boots (42.3%), and mask (43.2%). The PPE worn (except for an apron) was proportionally higher in farmers than in farm workers. There is considerable evidence to suggest that the significant determinants associated with PPE use and pesticide safety practices are as follows: (1) demographic factors (i.e. education/literacy level, experience of illness, income); (2) farm structure factors (i.e. farm size); (3) behavioral and psychosocial factors (i.e. contact with pesticides, perceptions, attitudes, awareness, norms and beliefs); and (4) environmental factors (i.e. information about pesticides, access to extension services, training program, and farm organization). Therefore, there is a recognizable need for a life-long education program with training to change the perception and behavior of pesticide handlers sustainably.